Unveilling Nationalism Within Religious Moderation: A Case Study - Nikmah, Faridatun; Pramitha, Devi; Anggarini, Ida Fitri; Noviyanti, Shobihatul Fitroh (Dawuh Guru: Jurnal Pendidikan MI/SD, 2024)
Religious moderation is needed due to the fact that happened today. This study aimed to explore the values of religious moderation on the primary level at MI Miftahul Huda Ngadireso Poncokusumo which gained the MURI Record. This qualitative descriptive study used observation, in-depth interviews, and documentation to collect primary data from the headmaster, five teachers, and fifteen fifth-grade students. The result shows that long before the launching of religious moderation, this school has been implementing the values of religious moderation till reached the achievement. The respondents also add some statements that religious moderation is important specifically as a provision for primary students to improve nationalism, tolerance, against violence, and adaptation to local culture. The findings indicate that amar ma’ruf nahi munkar is implemented frequently.